The trajectory of cognitive decline and neuropathological features among APOEɛ2 carriers: Genetics/genetic factors of Alzheimer's disease. (7th December 2020) - Gauthreaux, Kathryn; Teylan, Merilee; Culhane, Jessica E.; Miller, Zachary; Schwabe‐Fry, Kristen; Chen, Yen‐Chi; Chan, Kwun Chuen Gary; Mock, Charles; Kukull, Walter A.
Abstract: Background: Research on the APOEɛ2 allele and its role in neurodegenerative disease is sparse compared to APOEɛ4. Studies have indicated that ɛ2ɛ2 homozygosity is protective against developing Alzheimer's disease neuropathology (ADNP). Our goal was to explore cognitive trajectories and neuropathological features among APOEɛ2 carriers versus an ɛ3ɛ3 reference group. Method: Data were obtained from the National Alzheimer's Coordinating Center. Participants were included if they had neuropathology data available within 2 years of their most recent clinic visit. Due to sample size, we combined the ɛ2ɛ2 and ɛ2ɛ3 genotypes into one group for our analyses. Linear regression models with generalized estimating equations were run comparing the trajectory of CDR® Dementia Staging Instrument sum of boxes (CDR‐SB) over time between participants with ɛ2ɛ2/ɛ2ɛ3 or ɛ2ɛ4 to those with ɛ3ɛ3. Logistic regressions were run comparing the odds of having various neuropathological features in these groups. All models were stratified by baseline CDR global score (CDR) and adjusted for education, sex, race/ethnicity, smoking status, and hypercholesterolemia. Linear models additionally adjusted for age at baseline and accounted for repeated measures by individual, while logistic models examining neuropathological features adjusted for age at death. Result: We identified 356 ɛ2ɛ2/ɛ2ɛ3, 105 ɛ2ɛ4, and 1937 ɛ3ɛ3 participants with a mean follow‐up of 3.8, 4.1 and 3.7 years, respectively. Both ɛ2 carrier groups showed significant cognitive decline in CDR‐SB regardless of baseline CDR, although the slopes were not significantly different from the ɛ3ɛ3 group. When comparing the neuropathological features present in these groups, ɛ2ɛ2/ɛ2ɛ3 participants who were mildly impaired (i.e., CDR = 0.5) at baseline had significantly higher odds of FTLD‐tau pathology (p < 0.01) and lower odds of ADNP (p < 0.01) compared to ɛ3ɛ3 participants. Conclusion: In our sample, we found that ɛ2ɛ2/ɛ2ɛ3 participants displayed more FTLD‐tau at autopsy, but less ADNP compared to ɛ3ɛ3 participants. Our finding that ɛ2ɛ2/ɛ2ɛ3 participants had less ADNP supports the notion that ɛ2 is protective against ADNP, although when the ɛ4 allele is present it overrides the ɛ2 protective effects against ADNP. Despite this protective effect of the ɛ2ɛ2/ɛ2ɛ3 genotype against ADNP we found that the ɛ2ɛ2/ɛ2ɛ3 genotype did not prevent cognitive decline when compared to the ɛ3ɛ3 group.